Bio-treatment of Cheese Whey by Black Soldier Fly Larvae (Hermetia illucens) reared in Algeria - Hanafi, Tahar; Meziane, Kaci Zoubida; Megateli, Smain; Moussaoui, Badreddine; Guemou, Laid; Reghioui, Bachir (Future Science, 2024)
Whey, a by-product of cheese industry, poses environmental challenges when discharged untreated. This study aimed to mitigate whey pollution and transform it into value-added products using black soldier fly larvae (BSFL). By investigating whey effects on BSFL growth and performance, an innovative waste management strategy was explored. The five-old-day larvae were fed with four diets; dry spent coffee ground (SCG) as the control diet, while SCG wetted with acid, sweet and fermented whey were the test diets. The results showed that whey types increased significantly (p < 0.05) BSFL growth compared to the control, the dry weight (53.83±0.49 Vs 25.10±0.18 mg/larva), growth rate (1.59±0.06 Vs 0.44±0.01 mg/day) and survival rate (78.83±1.25 Vs 68.50±1.5 %) of larvae and reduced their development time (28.00±01 Vs 37.00±01 day). Furthermore, mixing SCG diet with whey enhanced positively their performance by increasing the waste reduction (26.73±0.81 Vs 16.87±0.37 %), waste reduction index (0.85±0.03 Vs 0.45±0.01 %/day), approximate digestibility (36.49±1.52 Vs 20.29±0.53 %) and bioconversion rate (17.94±0.47 Vs11.65±0.52%). Adding whey to SCG diet increased protein content of BSFL (40.11% vs. 34.18%) and reduced fat (36.06 vs. 37.87 %) in dry mass. Whey also improved the composition of frass by increasing the phosphorus and total nitrogen levels. This approach demonstrates a sustainable solution for dairy industries waste, contributing to the circular economy and offering potential applications in animal feed and fertilizer production.